(3JGL GddZI hUMGM GdYQHjIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3MdH s)
(3ChdgG (B:s
(3HGH GdKGA aUd GdCda (B: (3GdCHK GdCTjQ GdfTjW bGd CHh RQGQI GdfUQi CUHM YeGQ fTjWkG CHKkG jCcd dMeG HGjJkG bO cHKG s
(3BNQgG (B:s
(3hCfTO GdCMeQMJi GSJbGeJ dg GdBaGb WGFYI aeG jbGd dg gjO hdGgGO Ci dG jMQc hdG jefY ef TF hdG jRLQ Yfg Jbhd (B: (3gOJ GdQLd hgjOJg Yf jYbhH Je GdLRA GdKGfi efcJGH GdUMGM ai GddZI , jJdhg ai GdLRA GdKGdK HGH GdPGd , hGdMeO ddg s
(3HHYV ChQGbgG JbWjYs
(3fSNI MGOjI YTQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
Keywords: (3GddZIs